Effects of nitrogen forms on the activities of H+-ATPase and redox sysytem in tomato root plasmalemma under different light intensity - LIU Yong-hua; ZHU Zhu-jun; CHEN Xin-juan (浙江大学学报. 农业与生命科学版)
Effects of nitrogen forms on the physiological and biochemical characteristics of tomato root under different light intensity were investigated. The results indicated that under high light intensity ammonium treatment, compared with nitrate treatment, significantly decreased root biomass and root vigor, and significantly enhanced the activity of H+-ATPase and redox system of root plasmalemma, which resulted in the increase of the proton extrusion of roots simultaneously. Under low light intensity, Ammonium treatment had no significant effects on root biomass and root vigor, and the increase of the activity of H+-ATPase and redox system was less than that under high light intensity.